Iridescence from Total Internal Reflection at 3D Microscale Interfaces Mechanistic Insights and Spectral Analysis - Sturniolo, Nathaniel E (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 The Authors. Advanced Materials published by Wiley-VCH GmbH.